Structure and Inter-Annual Variability of the Freshened Surface Layer in the Laptev and East-Siberian Seas During Ice-Free Periods - Osadchiev, Alexander; Frey, Dmitry; Spivak, Eduard; Shchuka, Sergey; Tilinina, Natalia; Semiletov, Igor (Frontiers in Marine Science, 2021)
This work is focused on the structure and inter-annual variability of the freshened surface layer (FSL) in the Laptev and East-Siberian seas during ice-free periods. This layer is formed mainly by deltaic rivers among which the Lena River contributes about two thirds of the inflowing freshwater volume. Based on in situ measurements, we show that the area of this FSL during certain years is much greater than the area of FSL in the neighboring Kara Sea, while the total annual freshwater discharge to the Laptev and East-Siberian seas is 1.5 times less than to the Kara Sea (mainly from the estuaries of the Ob and Yenisei rivers). This feature is caused by differences in morphology of the estuaries and deltas. Shallow and narrow channels of the Lena Delta are limitedly affected by sea water. As a result, undiluted Lena discharge inflows to sea from multiple channels and forms relatively shallow plume, as compared to the Ob-Yenisei plume, which mixes with subjacent saline sea water in deep and wide estuaries. Due to small vertical extents of FSL in the Laptev and East-Siberian seas, wind conditions strongly affect its spreading and determine its significant inter-annual variability, as compared to relatively stable FSL in the Kara Sea. During years with prevailing western and northern winds, FSL is localized in the southern parts of the Laptev and East-Siberian seas due to southward Ekman transport, meridional extent (<250 km) and area (∼250,000 km2) of FSL are relatively small. During years with strong eastern winds FSL spreads northward over large area (up to 500,000 km2), its meridional extent increases up to 500–700 km. At the same time, area and position of FSL do not show any dependence on significant variability of the annual river discharge volume and ice coverage during warm season.